Hepatoprotective effect of Chichorium intybus L. on liver toxicity in rat - H Madani; S Asgary; GH Naderi; M Talebolhoseini (Institue of Medicinal Plants, ACECR, 2006)
Background: Plant phenolic compounds such as flavonoids have important role in treatment of many diseases. Also some of them have potent hepatoprotective effects. Objective: In this study, we have investigated the protective effects of polyphenolic extracts of Silybum marianum and Chichorium intybus on thioacethamide-induced hepatotoxicity in rat. Methods: Extracts were injected to rats, at a dose of 25 mg/kg body weight together with thioacetamide at a dose of 50 mg/kg body weight. For investigation of the hepatoprotective effect of extracts against thioacetamide, activity of aminotransferases (SGOT and SGPT), alkalin phosphatase, bilyrubin, Na+ and K+ were measured. Results: significant decreases were observed in activities of aminotransferases, alkalin phosphatase and bilyrubin in groups that treated with extracts together with thioacetamide in comparation with thioacetamide treated group. Level of Na+,K+ and liver weight betwen different groups had not significant different. Conclusions: This results showed protective effect of chichorium extracts on thioacetamide-induced hepatotoxicity in rat.